2020
DOI: 10.1111/wre.12410
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting seed germination and emergence of Aegilops tauschii

Abstract: Information on seed germination and emergence ecology of Aegilops tauschii is scant, despite it being a widespread invasive weed in China. We conducted this study to determine the effects of various factors on seed germination and seedling emergence in three A. tauschii populations. Seeds germinated across a wide range of temperatures (5–35°C), with germination of over 90% at 15–20°C. Germination was completely inhibited when dry seeds were exposed to a temperature of 160°C for 5 min; a similar response was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 42 publications
3
19
0
Order By: Relevance
“…In comparison with control (0 MPa), the minimum germination was reported at 40 • C under −2.0 MPa, while the maximum was reported at 20 • C under −0.5 MPa, indicating that GP decreased as T decreased (Figure 1a-f). These findings are in agreement with the previous studies that have indicated that temperature is a critical factor that negatively impacts seed germination by influencing the GP and GR in a wide range of plant species [16,18,57]. In the present study, GP increased with the accelerated aging period (AAP) and significantly (p ≤ 0.05) decreased with high temperature.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In comparison with control (0 MPa), the minimum germination was reported at 40 • C under −2.0 MPa, while the maximum was reported at 20 • C under −0.5 MPa, indicating that GP decreased as T decreased (Figure 1a-f). These findings are in agreement with the previous studies that have indicated that temperature is a critical factor that negatively impacts seed germination by influencing the GP and GR in a wide range of plant species [16,18,57]. In the present study, GP increased with the accelerated aging period (AAP) and significantly (p ≤ 0.05) decreased with high temperature.…”
Section: Discussionsupporting
confidence: 94%
“…Further, the θH values increased with an increase in cardinal Ts up to T o and then linearly decreased with a decrease in T > T o . Previous studies have also demonstrated that the values of θH have increased at suboptimal temperatures for potato [57] and watermelon [12,40].…”
Section: Discussionmentioning
confidence: 87%
“…Among these abiotic factors, T is one of the devastating stress affecting seed germinations in several plants [ 31 , 32 ]. Stress related to water ( ѱ) is also major environmental factor limiting early seedling and seed germination [ 33 , 34 ]. Our results also demonstrated that seed germination was significantly affected by T and water stress ( ѱ ).…”
Section: Discussionmentioning
confidence: 99%
“…Seed germination is crucial for uniform and maximum crop production ( Carrera-Castaño et al, 2020 ), and the optimization of intrinsic and extrinsic factors is very important for promoting the transition from dormancy to germination ( Figure 1 ) ( Wang et al, 2020 ). The dormancy level of commercial crop varieties is typically lower than that of their wild relatives, as this helps to achieve maximum production.…”
Section: Introductionmentioning
confidence: 99%